Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1128/aem.02806-15
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Decrease the Viability of Cryptosporidium parvum Oocysts

Abstract: dOocysts of the waterborne protozoan parasite Cryptosporidium parvum are highly resistant to chlorine disinfection. We show here that both silver nanoparticles (AgNPs) and silver ions significantly decrease oocyst viability, in a dose-dependent manner, between concentrations of 0.005 and 500 g/ml, as assessed by an excystation assay and the shell/sporozoite ratio. For percent excystation, the results are statistically significant for 500 g/ml of AgNPs, with reductions from 83% for the control to 33% with AgNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 29 publications
5
22
0
Order By: Relevance
“…Also, in Figure 2(c), the rupture of the membrane that encloses one of the sporocysts is observed; however, in Figure 2(c), this alteration is pronounced more strongly than Figure 2(b) (arrow). Although studies on the effect of AgNPs on T. gondii oocysts are not reported in the literature, similar results are shown in Cryptosporidium parvum, a human pathogen of the phylum Apicomplexa such as T. gondii, and Pamela Cameron et al evaluated the viability of oocysts exposed to AgNPs and silver ions [10], showed that both AgNPs and silver ions strongly decrease the viability of oocysts; however, the sporozoite/shell ratio was more affected with treatment with AgNPs possibly because sporozoites are destroyed by interaction with AgNPs.…”
Section: Morphology Alteration Of T Gondii Oocyst and S Braenderup mentioning
confidence: 79%
See 2 more Smart Citations
“…Also, in Figure 2(c), the rupture of the membrane that encloses one of the sporocysts is observed; however, in Figure 2(c), this alteration is pronounced more strongly than Figure 2(b) (arrow). Although studies on the effect of AgNPs on T. gondii oocysts are not reported in the literature, similar results are shown in Cryptosporidium parvum, a human pathogen of the phylum Apicomplexa such as T. gondii, and Pamela Cameron et al evaluated the viability of oocysts exposed to AgNPs and silver ions [10], showed that both AgNPs and silver ions strongly decrease the viability of oocysts; however, the sporozoite/shell ratio was more affected with treatment with AgNPs possibly because sporozoites are destroyed by interaction with AgNPs.…”
Section: Morphology Alteration Of T Gondii Oocyst and S Braenderup mentioning
confidence: 79%
“…Other studies report important applications of the use of AgNPs to affect protozoan parasites pathogenic for human health and that present mechanisms of resistance to chlorine treatments. Cameron et al demonstrated in their study breakdown of the cell structure of oocysts Cryptosporidium parvum when exposed to AgNPs, revealing a significant decrease in the viability of the oocysts of the parasite [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli , Pseudomonas spp . and the protozoan pathogen Cryptosporidium [ 12 , 36 , 37 ]. When comparing S .…”
Section: Discussionmentioning
confidence: 99%
“…They have been used in wound dressings and commercial antimicrobial socks. Recently, silver nanoparticles were shown to kill the chlorine-resistant apicomplexan parasite Cryptosporidium parvum [162]. Many pathogens have become resistant to conventional disinfectants, necessitating increasing dosage and mixtures of disinfectants that may produce harmful by-products.…”
Section: Antimicrobial Materialsmentioning
confidence: 99%